2019
DOI: 10.1111/nep.13489
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of chronic kidney disease in China: A national study based on hospitalized patients from 2010 to 2015

Abstract: The spectrum of CKD is changing in China, with variations over time and geographic regions, which has implication regarding developing the prevention strategy of CKD. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…As the fastest growing region in China's economy, Shanghai places great emphasis on general practice and public health, and community health service development is also of paramount importance. The characteristics of this city are as follows: first, comparatively, the overall health of its residents are similar to that of individuals in developed countries; second, the diversity within groups, such as urban vs. rural inhabitants and individuals of different sexes and ages, may contribute to differences in the utilization of primary care institutions [10]. Therefore, it is very important to analyse primary care utilization to inform the allocation of resources and support the development of functional community healthcare centres in this region.…”
Section: Introductionmentioning
confidence: 99%
“…As the fastest growing region in China's economy, Shanghai places great emphasis on general practice and public health, and community health service development is also of paramount importance. The characteristics of this city are as follows: first, comparatively, the overall health of its residents are similar to that of individuals in developed countries; second, the diversity within groups, such as urban vs. rural inhabitants and individuals of different sexes and ages, may contribute to differences in the utilization of primary care institutions [10]. Therefore, it is very important to analyse primary care utilization to inform the allocation of resources and support the development of functional community healthcare centres in this region.…”
Section: Introductionmentioning
confidence: 99%
“…34 Diabetes and hypertension were reported to be the major causes of kidney disease in China. 35 We found that the highest incidence rate of ESKD was in Northeast China. The high prevalence but low control rate of diabetes and hypertension might be the leading cause of that.…”
Section: Discussionmentioning
confidence: 79%
“…Previously, we performed a validation study using data from 67,376 patients from 3 hospitals in the Hospital Quality Monitoring System data set, which are the pilot hospitals that accomplished the Hospital Quality Monitoring System phase II data collection expansion to the data from laboratory tests. 10 CKD was defined as the presence of proteinuria and/or an estimated glomerular filtration rate less than 60 mL/min per 1.73 m 2 . The sensitivity and specificity of CKD identification by International Classification of Diseases, 10th revision, coding was 34.2% and 97.8%, respectively; which explained the relatively low percentage of CKD among the hospitalized population.…”
Section: Summary Of the Current Adr Section I Chronic Kidney Diseasementioning
confidence: 99%